Return on Assets, Likuiditas dan Ukuran Perusahaan Terhadap Struktur Modal - Marwan Effendi; Nugraha Nugraha (Universitas Muhammadiyah Prof. DR HAMKA., 2018)
The purpose of this research is to know the effect of ROA, Liquidity and Firm Size on Capital Structure of Micro Finance Institution Company (LKM) registered in Otoritas Jasa Keuangan in 2016 up to Mei 2017. The object of research which then operationalized consists of Return On Assets (ROA), Liquidity and Firm Size as independent variable and Capital Structure is operated as dependent variable. The method in this research is quantitative verification. The population used is a conventional Microfinance Institution (LM) registered in the Otoritas Jasa Keuangan in 2016 up to May 2017 of 147 companies, and the financial data of that period from all populations is used for research samples. Data analysis technique using multiple linear regression statistic with simultaneous significance test with F test. The result of F Test statistic shows that regression model can be used to draw conclusion and predict about ROA, Liquidity, Firm Size to CapitalStructure in the future. Hypothesis test results accept that ROA, Liquidity and Company Size negatively affect the Capital Structure.